2022
DOI: 10.1177/18479790221097528
|View full text |Cite
|
Sign up to set email alerts
|

Linking customized logistics service in online retailing with E-satisfaction and E-loyalty

Abstract: Online retailers are providing customized logistics service to meet heterogeneous customer demand. However, the value of customized logistics service is not clear. We study conceptually and empirically how customized logistics service influences online customer post-purchase behavior, specifically e-satisfaction and e-loyalty. Primary data on customized logistics service were collected from an online field study involving direct observation. Secondary data on e-satisfaction and e-loyalty were collected from Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This can also be seen in previous research. Hu et al (2016) and Hu et al (2022) both highlight the positive impact of customised logistics services on online shoppers' satisfaction and loyalty. The findings in this study align with the work of Jain and Sundström (2021), who emphasised the importance of customisation in creating unique and satisfying customer experiences.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This can also be seen in previous research. Hu et al (2016) and Hu et al (2022) both highlight the positive impact of customised logistics services on online shoppers' satisfaction and loyalty. The findings in this study align with the work of Jain and Sundström (2021), who emphasised the importance of customisation in creating unique and satisfying customer experiences.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…After shipping and customers receive orders, the second survey (delivered by e-mail) asks about retailers' order fulfillment quality. Previous studies have reported details on the BizRate customer survey (Cho, 2014;Hu et al, 2022;Thirumalai & Sinha, 2011).…”
Section: Methodology Data Source and Collectionmentioning
confidence: 99%
“…Consumer satisfaction refers to the degree of consumers’ psychological feelings and expectations regarding a particular product or service. 30,31 For example, UGC influences consumers' expectations, which indirectly affects consumer satisfaction 32 and contains information that helps companies understand user satisfaction. 33 Satisfaction also mediated the relationship between UGC and brand value.…”
Section: Existing Studies and Backgroundmentioning
confidence: 99%